Improving injury outcomes and experience of indigenous New Zealanders. (12th November 2014) - Witheford-Smith, Suzanne; Karaitiana, Ronald
Abstract : This presentation outlines disparities in the uptake of accident compensation entitlements by indigenous New Zealanders and a programme to prevent injury and improve outcomes/experience for Māori. ACC administers NZ's 24/7 no-fault accident compensation scheme which covers New Zealanders and visitors to NZ injured at work, home, play, in road crashes, or during treatment. Research has shown that disparities persist in injury outcomes/experience for NZ's indigenous population (Māori make-up 15% of the population and experience multiple disadvantage). This is inconsistent with the Government's commitment to Crown-Māori partnership. Disparities findings persist for Māori included; higher rates of serious/fatal injuries on the roads, lower GP referral rates to medical/surgical specialists, found the claim process more complicated and ACC less helpful in their return to work and lower rates of employment participation following a serious injury. ACC's 10 year vision of success; improved outcomes/experience for Māori clients and businesses, increased injury prevention effectiveness for Māori and improved ACC culture and capability in relation to Māori. Over a three year period, the ACC Board considered a series of papers on disparities in the uptake of entitlements by Māori. In early 2013, the Board considered advice on the Scheme's and organisation's responsiveness to Māori and endorsed the need for significant improvements. We shall explore two phases. Phase 1 of ACC's Māori Programme aims to reduce disparities, build organisational capability and establish relationships. Initiatives include innovative solutions to improve employment participation of seriously injured Māori. Phase 2 builds new partnerships with indigenous organisations and embeds cultural-responsiveness into the organisation/system. Challenges include building genuine partnerships and sustaining the Programme in a changing organisational, social, political and economic context. Improving injury outcomes/experience for Māori is a long-term commitment. Programme success includes fewer fatal/serious injuries to Maori, better employment participation after injury, and new partnerships.